Banded For Trouble! A Case Report On Chronic Midgut Volvulus In A 70-Year-Old Due To Ladd's Band With A Review Of Literature - Mukherjee, Risheen; Longkumer, Akumlong; Kolte, Shubham S; Banerjee, Soumya; Karmakar, Nisith Chandra (Journal of Society of Surgeons of Nepal, 2024)
Background: Midgut volvulus is a rare but serious condition caused by the twisting of the intestines around the superior mesenteric artery (SMA), often associated with intestinal malrotation. It can present in both pediatric and adult populations, with adults experiencing a more chronic presentation. The condition may be complicated by the presence of Ladd’s bands, fibrous structures that can obstruct the duodenum and lead to bowel ischemia. Case Report: A 70-year-old female presented with a three-month history of solid food intolerance, recurrent bilious vomiting, and generalized limb swelling. Physical examination revealed pallor, abdominal distension, and severe limb oedema, with chest X-ray showing bilateral pleural effusion. Ultrasound indicated collapsed small bowel with mild ascites. Contrast-enhanced CT showed a severely dilated stomach and duodenum, with a characteristic "corkscrew" sign indicating volvulus. Laparotomy revealed clockwise rotation of the small bowel around the SMA and Ladd’s bands compressing the duodenum. Adhesiolysis and mesenteric widening were performed, and the bowel was repositioned. The patient was discharged on postoperative day 4, symptom-free, with follow-up at six months showing no recurrence. Conclusion: Midgut volvulus is a rare but critical condition in adults, often presenting with nonspecific symptoms. Timely diagnosis and surgical intervention are crucial to prevent severe complications such as bowel ischemia and gangrene.